Teknologi Blockchain dalam Keamanan Sertifikat Menggunakan Smart Contracts dan Distributed Ledger pada Platfrom Edutech - Seni Oknora Firza; Y Yuhandri; S Sumijan (LPPM STIKOM Tunas Bangsa, 2024)
The ever-increasing development of the digital environment means that educational certificates are often vulnerable to forgery, manipulation, or even loss of integrity. Blockchain is a technology that allows for a distributed database that can only be accessed by a certain number of computer network nodes. Distributed Ledger Technology (DLT) is a system that captures and distributes data over multiple data stores (Ledgers), where each storage has identical data records. Smart Contracts is a Blockchain protocol that allows developers to create and execute financial agreement codes on the Blockchain. This contract will be activated by all parties involved. This research aims to improve the security of certificate authenticity on the edutech platform at Inatechno. The methods applied are Smart Contract and Distributed Ledger. The dataset processed in this research comes from Inatechno. The dataset consists of 48 data on certificate participants who have taken part in training activities at Inatechno. The results of this research are that Blockchain technology can increase certificate security on the Edutech platform. The resulting system can automate the verification process and reduce the risk of counterfeiting. Therefore, this research can be a reference that Blockchain technology using Smart Contracts and Distributed Ledger can be an effective solution in increasing certificate security on the Edutech platform. This implementation can provide significant benefits in supporting the need for security and integrity of certificate data, opening up the potential for further development in the context of digital education.